Perbedaan Orientasi Pendidikan Islam Dengan Pendidikan Non-Islam - M. Hafiz Alfiandi; Rendy Ardiansyah; M.Fahri; Putri Nabila; Afrahul Fadhila Daulay (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
First of all, let's understand between Islamic education and non-Islamic education. The orientation of Islamic education is when the education system is based on the values, teachings and principles of the Islamic religion, while non-Islamic education refers to an education system that is not based on a particular religion. The problem that arises is when there is an imbalance between these two orientations. Some people argue that the orientation of Islamic education can ignore important aspects of non-Islamic education such as science, technology, arts and culture. On the other hand, there are those who argue that non-Islamic education can ignore the values ​​and religious principles that are important for the majority of Muslims.